Liquid curable silicone rubber and preparation method thereof
By adding treated zirconium dioxide pre-crosslinked structure to the silicone rubber coating of automobile airbags, the problem of insufficient wear and tear resistance in the prior art is solved, and the wear and tear resistance of the coating is significantly improved, ensuring the long-term functional integrity of the airbag.
Patent Information
- Application Number
- CN202510002330.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-15
AI Technical Summary
The existing silicone rubber coatings have problems with insufficient anti-wear and tear resistance in automotive airbags, resulting in incomplete function during long-term operation.
Using a liquid curable silicone rubber composition, the crosslinking density and compatibility of the silicone rubber are enhanced by adding a treated zirconium dioxide pre-crosslinking structure to the system, thereby enhancing the wear resistance and tear resistance of the coating.
It significantly improves the wear and tear resistance of the silicone rubber coating, allowing the car airbag to maintain functional integrity during long-term operation and extend its service life.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of silicone rubber, and in particular relates to liquid curable silicone rubber which can be coated on the surface of fabric and a preparation method thereof. Background Art
[0002] With the rapid growth of social economy, the car ownership rate of Chinese residents has increased rapidly, but the traffic accident casualties have become more and more serious, which has caused huge losses to social and economic development. Therefore, the safety issues related to automobiles have received more and more attention, and the safety performance of the vehicle itself and the human protection performance are aspects that cannot be ignored in the development of automobiles.
[0003] As an indispensable part of automobile safety devices, automobile airbags have higher and higher requirements for their protective performance as automobiles continue to develop. The main part of the airbag is composed of an airbag. When the vehicle is hit by an external impact, the gas in the airbag will inflate the airbag in a short time to form an air cushion, thereby buffering the human body in the impact and effectively protecting the human body from injury or reducing the injury. Among them, coating the surface of the airbag can effectively prevent the gas from escaping from the airbag and can effectively protect the airbag from damage. Therefore, the good performance of the coating on the surface of the airbag is crucial.
[0004] During the daily operation of the car, the airbag is in a folded and compressed state. Only when the car body is hit or in other unfavorable situations, the airbag will inflate and pop out to protect the human body. If the airbag is subjected to vibration or mechanical wear and other factors during the long-term operation of the car, and surface defects occur, the defects will cause the airbag to have weak points, which will seriously affect the performance of the airbag. Therefore, to ensure that the airbag can work effectively and effectively protect the human body when triggered even after many years, the coating on the airbag must have long-term anti-aging, anti-wear and anti-tearing effects, so that the airbag can work well when inflated by gas.
[0005] CN10374027B adds modified MQ resin to a silicone rubber composition, and forms a film after curing on the fabric surface, but no further research is done on its wear and tear resistance. CN106254002B uses a cationic resin treated with γ-glycidyloxypropyltrimethoxysilane as a tackifier and adds it to a liquid silicone rubber composition. After curing, the friction resistance of the coating is 1000-1700 times, and the wear resistance level is poor, which needs to be further improved.
[0006] Therefore, it is necessary to provide a new type of anti-wear additive to improve the wear and tear resistance of silicone rubber coatings. Summary of the invention
[0007] To solve the above problems, the present invention provides a liquid curable silicone rubber and a preparation method thereof. The silicone rubber can be coated on the surface of a fabric and has excellent wear resistance and tear resistance. The coating formed by curing the silicone rubber on the surface of the fabric is applied to the field of airbags, which can make the airbag have good wear resistance and tear resistance, thereby increasing the service life of the product and ensuring the functional integrity of the airbag during long-term operation of the vehicle.
[0008] A liquid curable silicone rubber, the raw materials of which include component A and component B,
[0009] The component A comprises the following components in parts by weight:
[0010] Base A: 50-70 parts
[0011] Vinyl silicone oil A: 20-40 parts
[0012] Catalyst: 1-5 parts
[0013] Stabilizer: 0.1-1 part
[0014] Component B includes the following components in parts by weight:
[0015] Base glue B: 50-70 parts
[0016] Vinyl silicone oil B: 20-30 parts
[0017] Cross-linking agent: 5-10 parts
[0018] Wear and tear resistant additives 1-10 parts
[0019] Preferably, the gum base A and gum base B are the same or different, and are preferably prepared using the same vinyl silicone oil, and are respectively prepared by mixing vinyl silicone oil C, silicon dioxide and a hydrophobic treatment agent.
[0020] Preferably, the mass ratio of the vinyl silicone oil C, silicon dioxide and hydrophobic treatment agent is 80-120:30-50:5-10.
[0021] The silica generally used for reinforcement includes pyrogenic silica / fumed silica / and silica formed by gel method. Fumed silica is generally preferred. The specific surface area of silica powder is preferably 50 m 2 / g or more, more preferably 100 to 300 m 2 / g, if the specific surface area is less than 50m 2 / g, its poor compatibility with the composition cannot satisfy the desired reinforcement effect.
[0022] The hydrophobic treatment agent used includes hydrolyzable organosilicon monomers such as chlorosilane, alkoxysilane and silazane. Preferably, the hydrophobic treatment agent includes chlorosilanes such as trimethylchlorosilane and dimethyldichlorosilane, silane coupling agents such as methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, and silazanes such as hexamethyldisilazane, among which silane coupling agents or silazanes are preferred.
[0023] Preferably, the base glue is prepared by mixing silicon dioxide, vinyl silicone oil C and a hydrophobic treatment agent.
[0024] Preferably, vinyl silicone oil A, vinyl silicone oil B, and vinyl silicone oil C may be the same or different, and preferably the same vinyl silicone oil is used, which are linear organopolysiloxanes having at least two vinyl groups bonded to silicon atoms, wherein the viscosity of the vinyl silicone oil is generally selected to be 10000-100000 mPa·S at 25°C, more preferably 10000-60000 mPa·S. When the viscosity is low, the silicone rubber coating obtained after curing has low strength and poor mechanical properties; when the viscosity is high, the viscosity of the obtained silicone rubber composition increases, which is not conducive to coating operations.
[0025] In component A, the catalyst is a platinum catalyst, preferably a platinum (0) catalyst solution coordinated by divinyltetramethyldisiloxane, namely, a Custer catalyst, which has good compatibility with the system and high catalytic activity.
[0026] In component A, the stabilizer is a compound that inhibits the platinum catalyst during the curing process, and is selected from acetylene alcohol compounds such as dimethyl-1-hexynol, 3-methyl-1-pentyn-3-ol or 3,5-dimethyl-1-pentyn-3-ol; preferably 3-methyl-1-pentyn-3-ol.
[0027] In component B, the crosslinking agent is a linear organopolysiloxane containing at least three hydrogen atoms bonded to silicon atoms, which undergoes a hydrosilylation addition reaction with the vinyl group in the vinyl silicone oil under the action of a catalyst to cure, thereby curing the composition on the surface of the fabric. Preferably, the crosslinking agent is selected from hydrogenated silicone oil with a viscosity of 10-30 mPa·S at 25°C, and more preferably hydrogenated silicone oil with a viscosity of 10-20 mPa·S.
[0028] In component B, the preparation method of the wear-resistant and tear-resistant additive is as follows: zirconium dioxide is first treated with a silane coupling agent containing ethylene double bonds, and then subjected to a hydrosilylation reaction with terminal hydrogen-containing silicone oil.
[0029] Zirconium dioxide powder has the physical and chemical properties of high hardness, low thermal conductivity, wear resistance, high stability and corrosion resistance. The introduction of zirconium dioxide powder can improve the mechanical properties of silicone rubber coating. However, as an inorganic oxide, zirconium dioxide has poor compatibility with the silicone oil system, uneven dispersion and easy agglomeration, so direct addition will cause performance degradation. The end of the grafted silicone oil segment has a reactive silicon hydrogen group, which makes the zirconium dioxide powder a pre-crosslinking point structure containing the grafted silicone oil segment. Adding this structure to silicone rubber can not only improve the compatibility of zirconium dioxide powder in the system so that it is more evenly dispersed, but also increase the crosslinking density of silicone rubber at this structure, greatly improving the mechanical properties of the coating. After the fabric surface is coated with liquid curable silicone rubber, the coating formed on the fabric surface has excellent wear resistance and tear strength, which can meet the functional integrity of automobile airbags during long-term operation and even under certain extreme conditions.
[0030] Among them, the silane coupling agent containing vinyl double bonds is selected from one of vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane or a mixture of two or more thereof.
[0031] The viscosity of the hydrogen-terminated silicone oil is 10-100 mPa·S at 25°C, more preferably 20-50 mPa·S.
[0032] Preferably, the mass ratio of the zirconium dioxide to the silane coupling agent containing ethylene double bonds is 1:1.2-1:2.0, more preferably 1:1.2-1:1.5; the mass ratio of the zirconium dioxide treated with the silane coupling agent containing ethylene double bonds to the terminal hydrogen-containing silicone oil is 1:1.1-1:1.2, and the zirconium dioxide treated with the silane coupling agent containing ethylene double bonds and the terminal hydrogen-containing silicone oil are subjected to a hydrosilylation reaction to graft the hydrogen-containing silicone oil chain segments under the action of a platinum catalyst to obtain a wear-resistant and tear-resistant additive with a pre-crosslinking point structure containing grafted silicone oil segments.
[0033] Preferably, the reaction temperature of zirconium dioxide and the silane coupling agent containing ethylene double bonds is 80°C-90°C, and the treatment time is 1-5h, preferably, the treatment time is 3-5h; the hydrosilylation reaction temperature is 60°C-70°C, and the hydrosilylation reaction time is 1-2h.
[0034] The present invention also provides a method for preparing the liquid curable silicone rubber. The liquid curable silicone rubber can be obtained by uniformly mixing component A and component B.
[0035] Preferably, the mass ratio of component A to component B is 1:1-1:1.2.
[0036] Preferably, component A and component B are mixed evenly in a high-speed dispersing homogenizer, and the mixed liquid silicone rubber coating liquid is evenly coated on the surface of the PET fabric, with a coating amount of 30-50g / m 2 , and cured at 150-180°C to obtain a cured coating on the fabric surface.
[0037] Compared with the prior art, the present application has the following beneficial effects: the liquid curable silicone rubber composition prepared by the present invention can not only improve its compatibility in the system and thus disperse more evenly by adding a treated zirconium dioxide pre-cross-linked structure into the system, but also increase the cross-linking density of the silicone rubber at the structure, so that the coating applied on the surface of the fabric has better mechanical properties, which is mainly manifested in that the coating has excellent wear resistance and tear strength. DETAILED DESCRIPTION
[0038] Source of raw materials:
[0039] Vinyl-terminated silicone oil (10000mPa·S, 25℃, SK-SOV-1WL), vinyl-terminated silicone oil (40000mPa·S, 25℃, SK-SOV-4WL), vinyl-terminated silicone oil (60000mPa·S, 25℃, SK-SOV-6WL), Shenzhen Tianqi New Material Technology Co., Ltd.; fumed silica (AEROSIL 200), Degussa silica;
[0040] Hexamethyldisilazane (≥99%), New Asia Strong Silicon Chemical Co., Ltd.
[0041] Platinum catalyst (Pt5000), Shaanxi Ruike New Materials Co., Ltd.;
[0042] Stabilizer (3-methyl-1-pentyn-3-ol, ≥98%), Shanghai Aladdin Reagent Co., Ltd.;
[0043] Cross-linking agent (20 mPa·S, 25°C, RH-H510) Ningbo Runhe High-tech Materials Technology Co., Ltd.
[0044] End-hydrogenated silicone oil (20 mPa·S, 25°C, RH-H45), End-hydrogenated silicone oil (40 mPa·S, 25°C, RH-DH07), End-hydrogenated silicone oil (70 mPa·S, 25°C, RH-DH04) Ningbo Runhe High-tech Materials Technology Co., Ltd.;
[0045] γ-Methacryloxypropyltrimethoxysilane (≥97%), Shanghai MacLean Biochemical Technology Co., Ltd.; Vinyltrimethoxysilane (≥99%), Shandong Sike New Materials Co., Ltd.;
[0046] Vinyltriethoxysilane (≥98%), Anaiji Chemical Reagent Co., Ltd.
[0047] Preparation Example 1
[0048] 80 parts by weight of vinyl-terminated silicone oil with a viscosity of 10000 mPa·S and a specific surface area of 200 m 2 / g fumed silica powder 40 parts by mass, hexamethyldisilazane 7 parts by mass and deionized water 2 parts by mass were added into a kneader in sequence and treated at room temperature for 1 hour. After that, the temperature was raised to 150°C and the vacuum pump was turned on to 10 mbar. After continuing the treatment for 2 hours, the temperature was lowered to room temperature, 20 parts by mass of 10000 mPa·S terminal vinyl silicone oil were added, and the base rubber was obtained after treating at room temperature for 1 hour.
[0049] Preparation Example 2
[0050] 90 parts by weight of vinyl-terminated silicone oil with a viscosity of 40000 mPa·S and a specific surface area of 200 m 2 / g fumed silica powder 45 parts by mass, hexamethyldisilazane 10 parts by mass and deionized water 2 parts by mass were added into a kneader in sequence and treated at room temperature for 1 hour. After that, the temperature was raised to 150°C and the vacuum pump was turned on to 10 mbar. After continuing the treatment for 2 hours, the temperature was lowered to room temperature, 20 parts by mass of 40000 mPa·S terminal vinyl silicone oil were added, and the base rubber was obtained after treating at room temperature for 1 hour.
[0051] Preparation Example 3
[0052] 80 parts by weight of vinyl-terminated silicone oil with a viscosity of 60000 mPa·S and a specific surface area of 200 m 2 / g fumed silica powder 30 parts by mass, hexamethyldisilazane 5 parts by mass and deionized water 2 parts by mass were added into a kneader in sequence and treated at room temperature for 1 hour. After that, the temperature was raised to 150°C and the vacuum pump was turned on to 10 mbar. After continuing the treatment for 2 hours, the temperature was lowered to room temperature, 20 parts by mass of 60000 mPa·S terminal vinyl silicone oil were added, and the base rubber was obtained after treating at room temperature for 1 hour.
[0053] Preparation Example 4
[0054] Weigh 20 parts by mass of zirconium dioxide powder ground in a mortar and add it into a flask, add 25 parts by mass of γ-methacryloxypropyltrimethoxysilane solution thereto, stir at 80°C for 5 hours, then cool to room temperature, add 0.04 parts by mass of platinum catalyst thereto, and stir evenly.
[0055] In another flask, 50 parts by mass of 20 mPa·S end-hydrogenated silicone oil was added, the temperature was raised to 60° C., and the zirconium dioxide powder treated with the coupling agent was slowly added to the flask. After the warm shock, the reaction was continued for 1 hour to obtain a wear-resistant and tear-resistant additive.
[0056] Preparation Example 5
[0057] Weigh 20 parts by mass of zirconium dioxide powder ground in a mortar and add it into a flask, add 25 parts by mass of γ-methacryloxypropyltrimethoxysilane solution thereto, stir at 80°C for 5 hours, then cool to room temperature, add 0.04 parts by mass of platinum catalyst thereto, and stir evenly.
[0058] In another flask, 50 parts by mass of 40 mPa·S end-hydrogenated silicone oil was added, the temperature was raised to 60° C., and the zirconium dioxide powder treated with the coupling agent was slowly added to the flask. After the warm shock, the reaction was continued for 1 hour to obtain a wear-resistant and tear-resistant additive.
[0059] Preparation Example 6
[0060] Weigh 20 parts by mass of zirconium dioxide powder ground in a mortar and add it into a flask, add 25 parts by mass of γ-methacryloxypropyltrimethoxysilane solution thereto, stir at 80°C for 5 hours, then cool to room temperature, add 0.04 parts by mass of platinum catalyst thereto, and stir evenly.
[0061] In another flask, 50 parts by mass of 70 mPa·S end-hydrogenated silicone oil was added, the temperature was raised to 60° C., and the zirconium dioxide powder treated with the coupling agent was slowly added to the flask. After the warm shock, the reaction was continued for 1 hour to obtain a wear-resistant and tear-resistant additive.
[0062] Preparation Example 7
[0063] Weigh 20 parts by mass of zirconium dioxide powder ground in a mortar and add it into a flask, add 25 parts by mass of vinyltrimethoxysilane solution, stir at 80°C for 5 hours, then cool to room temperature, add 0.04 parts by mass of platinum catalyst, and stir evenly.
[0064] In another flask, 50 parts by mass of 40 mPa·S end-hydrogenated silicone oil was added, the temperature was raised to 60° C., and the zirconium dioxide powder treated with the coupling agent was slowly added to the flask. After the warm shock, the reaction was continued for 1 hour to obtain a wear-resistant and tear-resistant additive.
[0065] Preparation Example 8
[0066] Weigh 20 parts by mass of zirconium dioxide powder ground in a mortar and add it into a flask, add 25 parts by mass of vinyltriethoxysilane solution, stir at 80°C for 5 hours, then cool to room temperature, add 0.04 parts by mass of platinum catalyst, and stir evenly.
[0067] In another flask, 50 parts by mass of 40 mPa·S end-hydrogenated silicone oil was added, the temperature was raised to 60° C., and the zirconium dioxide powder treated with the coupling agent was slowly added to the flask. After the warm shock, the reaction was continued for 1 hour to obtain a wear-resistant and tear-resistant additive.
[0068] Preparation Example 9
[0069] The difference from Preparation Example 5 is that 30 parts by mass of γ-methacryloxypropyltrimethoxysilane solution is added, and the rest is the same as Preparation Example 5.
[0070] Example 1
[0071] The raw material formula included in this embodiment includes the following component A and component B:
[0072] Component A includes the following components in parts by weight:
[0073] Base glue (preparation example 1): 60 parts
[0074] Vinyl silicone oil (10000mPa·S): 35 parts
[0075] Platinum catalyst: 1 part
[0076] Stabilizer 3-methyl-1-pentyn-3-ol: 0.2 parts
[0077] The preparation method of the above-mentioned component A is as follows: according to the formula and dosage of component A, the base rubber, vinyl silicone oil, platinum catalyst, and stabilizer (3-methyl-1-pentyn-3-ol) are added to a mixing tank, and then homogenized and mixed in a high-speed disperser homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component A.
[0078] Component B includes the following components in parts by weight:
[0079] Base glue (preparation example 1): 60 parts
[0080] Vinyl silicone oil (10000mPa·S): 30 parts
[0081] Cross-linking agent RH-H510: 10 parts
[0082] 4 parts of the wear-resistant and tear-resistant additive in Preparation Example 5
[0083] The preparation method of the above-mentioned component B is as follows: according to the formula and dosage of component B, the base rubber, vinyl silicone oil, crosslinking agent, and wear-resistant and tear-resistant additives are added to a mixing tank, and then homogenized and mixed in a high-speed dispersing homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component B.
[0084] Example 2
[0085] The raw material formula included in this embodiment consists of the following component A and component B:
[0086] The formula of component A is composed of the following components:
[0087] Base glue (Preparation Example 2): 60 parts
[0088] Vinyl silicone oil (40000mPa·S): 35 parts
[0089] Platinum catalyst: 1 part
[0090] Stabilizer 3-methyl-1-pentyn-3-ol: 0.2 parts
[0091] The preparation method of the above-mentioned component A is as follows: according to the formula and dosage of component A, the base rubber, vinyl silicone oil, platinum catalyst, and stabilizer (3-methyl-1-pentyn-3-ol) are added to a mixing tank, and then homogenized and mixed in a high-speed disperser homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component A.
[0092] The formula of component B is composed of the following components:
[0093] Base glue (Preparation Example 2): 60 parts
[0094] Vinyl silicone oil (40000mPa·S): 30 parts
[0095] Cross-linking agent RH-H510: 10 parts
[0096] 1 part of the wear-resistant and tear-resistant additive in Preparation Example 5
[0097] The preparation method of the above-mentioned component B is as follows: according to the formula and dosage of component B, the base rubber, vinyl silicone oil, crosslinking agent, and wear-resistant and tear-resistant additives are added to a mixing tank, and then homogenized and mixed in a high-speed dispersing homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component B.
[0098] Example 3
[0099] The raw material formula included in this embodiment consists of the following component A and component B:
[0100] The formula of component A is composed of the following components:
[0101] Base glue (Preparation Example 3): 60 parts
[0102] Vinyl silicone oil (60000mPa·S): 35 parts
[0103] Platinum catalyst: 1 part
[0104] Stabilizer 3-methyl-1-pentyn-3-ol: 0.2 parts
[0105] The preparation method of the above-mentioned component A is as follows: according to the formula and dosage of component A, the base rubber, vinyl silicone oil, platinum catalyst, and stabilizer (3-methyl-1-pentyn-3-ol) are added to a mixing tank, and then homogenized and mixed in a high-speed disperser homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component A.
[0106] The formula of component B is composed of the following components:
[0107] Base glue (Preparation Example 3): 60 parts
[0108] Vinyl silicone oil (60000mPa·S): 30 parts
[0109] Cross-linking agent RH-H510: 10 parts
[0110] 8 parts of the wear-resistant and tear-resistant additive in Preparation Example 5
[0111] The preparation method of the above-mentioned component B is as follows: according to the formula and dosage of component B, the base rubber, vinyl silicone oil, crosslinking agent, and wear-resistant and tear-resistant additives are added to a mixing tank, and then homogenized and mixed in a high-speed dispersing homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component B.
[0112] Example 4
[0113] The raw material formula included in this embodiment consists of the following component A and component B:
[0114] The formula of component A is composed of the following components:
[0115] Base glue (Preparation Example 2): 70 parts
[0116] Vinyl silicone oil (40000mPa·S): 30 parts
[0117] Platinum catalyst: 1 part
[0118] Stabilizer 3-methyl-1-pentyn-3-ol: 0.2 parts
[0119] The preparation method of the above-mentioned component A is as follows: according to the formula and dosage of component A, the base rubber, vinyl silicone oil, platinum catalyst, and stabilizer (3-methyl-1-pentyn-3-ol) are added to a mixing tank, and then homogenized and mixed in a high-speed disperser homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component A.
[0120] The formula of component B is composed of the following components:
[0121] Base glue (Preparation Example 2): 70 parts
[0122] Vinyl silicone oil (40000mPa·S): 25 parts
[0123] Cross-linking agent RH-H510: 6 parts
[0124] 4 parts of the wear-resistant and tear-resistant additive in Preparation Example 5
[0125] The preparation method of the above-mentioned component B is as follows: according to the formula and dosage of component B, the base rubber, vinyl silicone oil, crosslinking agent, and wear-resistant and tear-resistant additives are added to a mixing tank, and then homogenized and mixed in a high-speed dispersing homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component B.
[0126] Example 5
[0127] The raw material formula included in this embodiment consists of the following component A and component B:
[0128] The formula of component A is composed of the following components:
[0129] Base glue (Preparation Example 2): 70 parts
[0130] Vinyl silicone oil (40000mPa·S): 30 parts
[0131] Platinum catalyst: 1 part
[0132] Stabilizer 3-methyl-1-pentyn-3-ol: 0.2 parts
[0133] The preparation method of the above-mentioned component A is as follows: according to the formula and dosage of component A, the base rubber, vinyl silicone oil, platinum catalyst, and stabilizer (3-methyl-1-pentyn-3-ol) are added to a mixing tank, and then homogenized and mixed in a high-speed disperser homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component A.
[0134] The formula of component B is composed of the following components:
[0135] Base glue (Preparation Example 2): 70 parts
[0136] Vinyl silicone oil (40000mPa·S): 25 parts
[0137] Cross-linking agent RH-H510: 10 parts
[0138] 5 parts of the wear-resistant and tear-resistant additive in Preparation Example 5
[0139] The preparation method of the above-mentioned component B is as follows: according to the formula and dosage of component B, the base rubber, vinyl silicone oil, crosslinking agent, and wear-resistant and tear-resistant additives are added to a mixing tank, and then homogenized and mixed in a high-speed dispersing homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed component B.
[0140] Example 6
[0141] The silicone rubber was prepared by the same method as in Example 2, except that 4 parts of the wear-resistant and tear-resistant additive of Preparation Example 4 were added.
[0142] Example 7
[0143] The silicone rubber was prepared by the same method as in Example 2, except that 4 parts of the wear-resistant and tear-resistant additive of Preparation Example 6 were added.
[0144] Example 8
[0145] The silicone rubber was prepared by the same method as in Example 2, except that 4 parts of the wear-resistant and tear-resistant additive of Preparation Example 7 were added.
[0146] Example 9
[0147] The silicone rubber was prepared by the same method as in Example 2, except that 4 parts of the wear-resistant and tear-resistant additive of Preparation Example 8 were added.
[0148] Example 10
[0149] The silicone rubber was prepared by the same method as in Example 2, except that 4 parts of the wear-resistant and tear-resistant additive of Preparation Example 9 were added.
[0150] Comparative Example 1
[0151] The liquid curable rubber was prepared in the same manner as in Example 1, the main difference being that zirconium dioxide powder was added in an amount equal to the mass of the wear-resistant and tear-resistant additive.
[0152] Performance Testing:
[0153] Component A and component B were added into a mixing tank in a mass ratio of 1:1, and then homogenized and mixed in a high-speed dispersing homogenizer at a speed of 1500 rpm for 5 minutes to obtain a uniformly mixed liquid silicone rubber coating liquid.
[0154] Apply the mixed liquid silicone rubber coating liquid evenly on the surface of the PET fabric, with a coating amount of 30g / m 2 , and cured at 180°C for 1 min to obtain a cured coating on the fabric surface.
[0155] The obtained fabric with silicone rubber composition coating is subjected to bending friction resistance test using a shear bending friction tester. When the coating on the smooth surface of the fabric shows a streaky pattern, the number of load cycles experienced by the fabric is recorded; the force on the fabric when it is torn is tested using a tear force detection instrument.
[0156] Test sample Tensile strength(MPa) Friction resistance / times Tearing force / N Example 1 4.2 2200 300 Example 2 4.5 3000 380 Example 3 4.3 1800 320 Example 4 4.2 2800 360 Example 5 4.3 2600 350 Example 6 4.1 2500 340 Example 7 4.1 2600 340 Example 8 3.9 2200 280 Example 9 3.8 2100 300 Example 10 4.4 2700 350 Comparative Example 1 3.1 500 200
Claims
1. A liquid curable silicone rubber, characterized in that: Its raw materials include component A and component B. The component A comprises the following components in parts by weight: Base A: 50-70 parts Vinyl silicone oil A: 20-40 parts Catalyst: 1-5 parts Stabilizer: 0.1-1 part; Component B includes the following components in parts by weight: Base glue B: 50-70 parts Vinyl silicone oil B: 20-30 parts Cross-linking agent: 5-10 parts 1-10 parts of wear-resistant and tear-resistant additives.
2. The silicone rubber according to claim 1, characterized in that The base glue A and the base glue B are the same or different, and are respectively prepared by mixing vinyl silicone oil C, silicon dioxide and a hydrophobic treatment agent; Preferably, the mass ratio of the vinyl silicone oil C, silicon dioxide and hydrophobic treatment agent is 80-120:30-50:5-10; Preferably, the specific surface area of the silicon dioxide powder is preferably 50 m 2 / g or more, more preferably 100 to 300 m 2 / g; Preferably, the hydrophobic treatment agent comprises chlorosilane, alkoxysilane coupling agent or silazane, preferably silane coupling agent or silazane; More preferably, the hydrophobic treatment agent includes, but is not limited to, trimethylchlorosilane, dimethyldichlorosilane, methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, hexamethyldisilazane; Preferably, the base glue is prepared by mixing silicon dioxide, vinyl silicone oil C and a hydrophobic treatment agent.
3. The silicone rubber according to claim 1 or 2, characterized in that: Vinyl silicone oil A, vinyl silicone oil B, and vinyl silicone oil C are the same or different, preferably the same vinyl silicone oil, each of which is a linear organopolysiloxane having at least two vinyl groups bonded to silicon atoms, wherein the viscosity of the vinyl silicone oil at 25° C. is 10000-100000 mPa·S, more preferably 10000-60000 mPa·S.
4. The silicone rubber according to any one of claims 1 to 3, characterized in that: In component A, the catalyst is a platinum catalyst, preferably a platinum catalyst solution coordinated by divinyltetramethyldisiloxane; Preferably, in component A, the stabilizer is an acetylene alcohol compound, preferably selected from dimethyl-1-hexynol, 3-methyl-1-pentyn-3-ol or 3,5-dimethyl-1-pentyn-3-ol acetylene alcohol compounds; preferably 3-methyl-1-pentyn-3-ol.
5. The silicone rubber according to any one of claims 1 to 4, characterized in that: In component B, the crosslinking agent is a linear organopolysiloxane containing at least three hydrogen atoms bonded to silicon atoms; Preferably, the crosslinking agent is selected from hydrogenated silicone oil having a viscosity of 10-30 mPa·S at 25°C, more preferably hydrogenated silicone oil having a viscosity of 10-20 mPa·S.
6. The silicone rubber according to any one of claims 1 to 5, characterized in that: In component B, the preparation method of the wear-resistant and tear-resistant additive is as follows: zirconium dioxide is first treated with a silane coupling agent containing ethylene double bonds, and then subjected to a hydrosilylation reaction with terminal hydrogen-containing silicone oil; Preferably, the silane coupling agent containing vinyl double bonds is selected from vinyl trimethoxysilane, vinyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, methyl vinyl dimethoxysilane, methyl vinyl diethoxysilane, or a mixture of two or more thereof; Preferably, the viscosity of the hydrogen-terminated silicone oil is 10-100 mPa·S at 25°C, more preferably 20-50 mPa·S; Preferably, the mass ratio of the zirconium dioxide to the silane coupling agent containing ethylene double bonds is 1:1.2-1:2.0, more preferably 1:1.2-1:1.5; Preferably, the mass ratio of zirconium dioxide treated with a silane coupling agent containing ethylene double bonds to terminal hydrogen-containing silicone oil is 1:1.1-1:1.2; Preferably, the zirconium dioxide treated with a silane coupling agent containing ethylene double bonds is subjected to a hydrosilylation reaction with terminal hydrogen-containing silicone oil under the action of a platinum catalyst.
7. The silicone rubber according to any one of claims 1 to 6, characterized in that: The reaction temperature of zirconium dioxide and the silane coupling agent containing ethylene double bonds is 80°C-90°C, and the treatment time is 1-5h, preferably, the treatment time is 3-5h; And / or, the hydrosilylation reaction temperature is 60° C.-70° C., and the hydrosilylation reaction time is 1-2 h.
8. The method for preparing the liquid curable silicone rubber according to any one of claims 1 to 7, wherein the liquid curable silicone rubber is obtained by uniformly mixing component A and component B.
9. The preparation method according to claim 8, characterized in that: The mass ratio of component A to component B is 1:1-1:1.2; Preferably, component A and component B are mixed evenly in a high-speed dispersing homogenizer, and the mixed liquid silicone rubber coating liquid is evenly coated on the surface of the PET fabric and cured; Preferably, the coating amount is 30-50 g / m 2 , the curing temperature is 150-180℃.
Citation Information
Patent Citations
A Weighted Spectrum Detection Method Based on Signal Correlation Characteristics in Cognitive Networks
CN106254002B
Double-component addition-type liquid silicone rubber as well as preparation method of same
CN108219671A
Two-component flame-retardant liquid silicone rubber for insulator and preparation method thereof
CN109135299A
Reactive flame-retardant porcelainized powder and reinforced flame-retardant porcelainized organic silicon elastomer using same
CN113087969A
Liquid silicone rubber, preparation method and application thereof
CN113667310A